Thermal Resistance of the Loop Heat Pipe Prototype in Steady State Conditions - Haryanto, Dedy; Giarno, Giarno; Hatmoko, Sumantri; Pambudi, Yoyok Dwi Setyo; Kusuma, M. Hadi (Semesta Teknika, 2023)
The nuclear accident at the Fukushima Daiichi nuclear power plant in March 2011 in Japan caused a tsunami and submerged the emergency diesel generator resulting in a station blackout (SBO). Based on the accident, a study was conducted on the use of passive safety systems as a support for active safety systems in nuclear reactor cooling systems. The Loop Heat Pipe (LHP) prototype is a small-scale LHP research facility, one of which is used to determine the characteristics and heat transfer events in LHP. Calculations to determine the thermal resistance of the LHP prototype need to be carried out to determine its performance level. The research was carried out experimentally for data collection followed by calculations based on the data that had been obtained. The calculation results obtained that the lowest thermal resistance is 0.014 °C/w with a 100% filling ratio and an airflow velocity of 2.5 m/s, so the setting of filling ratio and airflow velocity produces the best LHP prototype performance. The higher the airspeed, the greater the heat released by the condenser resulting in the value of the thermal resistance of the LHP prototype getting smaller. Thus, the greater the airspeed, the lower the thermal resistance of the LHP prototype, this indicates that the performance of the LHP prototype is increasing.